KEMAMPUAN PEMECAHAN MASALAH DAN BERPIKIR KRITIS: ANALISIS KESALAHAN MAHASISWA PADA MATERI HOTS SMP - Ayathollah Khomeni; Yusup Junaedi; Yugi Hilmi; Rahmatika Elindra (JURNAL MathEdu (Mathematic Education Journal), 2026)
This study aims to analyze the problem-solving and critical thinking abilities of prospective mathematics teachers in solving Higher Order Thinking Skills (HOTS) problems on lines and angles through error analysis. The study employed a qualitative descriptive approach. The research subjects consisted of 20 fourth-semester students of the Mathematics Education Study Program at Institut Pendidikan Tapanuli Selatan (IPTS). Data were collected through HOTS geometry tests, task-based interviews, and documentation of students’ written work. Error analysis was conducted using Newman’s Error Analysis (NEA), while critical thinking and problem-solving abilities were analyzed using the FRISCO and Krulik-Rudnick frameworks. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results showed that students’ abilities were still in the moderate to low category. The dominant errors occurred at the transformation and process skills stages, indicating difficulties in converting visual representations into mathematical models and selecting appropriate solution strategies. In addition, students demonstrated weaknesses in critical thinking, particularly in reasoning, inference, and overview indicators. These errors were influenced by epistemological and ontogenic obstacles related to weak spatial ability and conceptual understanding of geometry. Therefore, HOTS-based learning emphasizing visualization, critical thinking, and systematic problem-solving is needed to improve prospective teachers’ mathematical abilities.